INOVASI IMPLEMENTASI E-HEALTH SEBAGAI MANIFESTASI SMART CITY DI KOTA YOGYAKARTA UNTUK MENINGKATKAN KUALITAS PELAYANAN KESEHATAN IBU DAN ANAK - Saharuddin, Erni (Natapraja, 2018)
The high public demand for quality improvement on KIA becomes the basic fundamentals for the government of Yogyakarta to upgrade the quality and efficiency of KIA services. One of the implemented policies is the application of smart city in the health sector, primarily focusing on e-Health development. This research aims reviewing innovation in the implementation of e-Health in health centers Mantrijeron by employing a qualitative approach with interviews, observation, and documentation. The results showed that innovation of e-Health was divided into four categories: man, money, methods and machine. In terms of man (human resources) there were Simpus facilitation officer and adequate number of qualified human resources. Meanwhile money innovation occurred by adequate financial support from APBD, BOK and BLUD budget. Method innovation came in with the application of SOP in each service which also describes the associated use of Simpus. Machine innovation occurred through adequate computer devices, efforts to restore the hardware restoration efforts, routine network maintenance by a team of Service Level Agreement (SLA) and assistance from the Department of Communications, Information and Coding of Yogyakarta City. Keywords: e-Health, SIMPUS, Innovation, Service Quality